Composite scintillators based on ZnWO4:Me+ micropowders obtained by solid-state synthesis - V.S. Tinkova; I.A. Tupitsyna; A.G. Yakubovskaya; L. Yu. Sidelnikova; S.O. Tretiyak; O.D. Opolonin (Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ: fìzika.)
The paper considers the possibility of using the method of heterovalent doping to improve the functional characteristics (light output and afterglow level) of composite scintillators based on ZnWO4 micropowder obtained by solid-stase synthesis. LiNO3, Li2SO4, Cs2SO4, Rb2SO4 were added to the mixture of initial ZnO and WO3 oxides in the amount of 0.003 wt. %. The synthesis was carried out in air at a temperature of 950 °C for 30 hours. The study of the morphology of the obtained powders was carried out by scanning electron microscopy (SEM). It has been shown that the grain size of the synthesized powders dependence on a greater extent by the radius of the cation replacing Zn2+ than by the presence of a mineralizer with a low melting point. The studied anions do not affect the synthesis process, and when ZnSO4 is added, the size of the obtained grains is similar to the nominally pure synthesized ZnWO4 (2-5 μm). When ZnWO4 is doped with 20% less Li+ relative to Zn2+, regardless of the form of introduction (anionic component), the average grain size increases by 4 times. When ZnWO4 doped with Rb+ and Cs+, which are twice as large as Zn2+, grains increase by a factor of 20. It happened because of a significant loosening of the crystal lattice formed by zero-dimensional defects, which contributes to better diffusion of reagents and acceleration of the synthesis process. The study of X-ray luminescence showed that the spectra of the synthesized powders coincide in terms of the peak position with the spectrum of the ZnWO4 single crystal, which corresponds to the emission on the WO6 6- oxyanion complex. The intensity of the bands increases with increasing dopant’s cationic radius: Li+ → Rb+ → Cs+. The maximum X-ray luminescence intensity is observed for the ZnWO4:Cs+ micropowder, which is two times higher than the intensity of the undoped ZnWO4 micropowder. This is due to a rather high degree of deformation of the structure of the WO6 emission center, which, in turn, affects the luminescent properties of the material. Composite samples based on the synthesized micropowders were prepared using SKTN optically transparent rubber as a binder in an amount of 50 wt.%. The results of measurements of the relative light output of composite scintillators based on ZnWO4:Me+ correlate with the results of measurements of the X-ray luminescence intensity of the synthesized powders. An increase in the value of the light output with an increase in the radius of the dopant cation is observed. Measurement of the afterglow level showed that the use of the heterovalent doping method, namely Me+ in our work, is an effective way to improve the scintillation parameters of crystalline materials. Composite scintillators based on ZnWO4:Cs+ and ZnWO4:Rb+ demonstrate the values of light output and afterglow at the level of a composite from a crushed ZnWO4 single crystal, and no worse than a single crystal ZnWO4 sample. The obtained materials are promising for use as scintillation detectors in computed tomography and digital radiography devices.